Incidence of human epidermal growth factor receptor-2 expression and its correlation with clinicopathological characteristics in gastric cancer at tertiary care centre at IGMC Shimla, Himachal Pradesh, India - Thakur, Vishal; Mahajan, Puneet; Sharma, Neelam; Sharma, Ved Kumar; Patial, Tushar; Singh, Biplav; Raina, Nidhi (International Surgery Journal, 2017)
Background: Trastuzumab has been approved for the treatment of patients with HER-2 positive metastatic/locally advanced adenocarcinoma of the stomach by FDA.1 Most of gastric cancer patients present at an advanced stage in our country, all patients of gastric adenocarcinoma should be subjected to HER-2 testing at initial diagnosis. Immunohistochemistry should be the initial testing methodology and Fluorescence in-situ hybridization should be used to retest immunohistochemistry 2+ samples. Methods: We conducted this study with the aim to establish the expression profile of HER-2 and its correlation to clinicopathological characteristics in resectable cases of gastric adenocarcinoma, in patients presenting with gastric adenocarcinoma at IGMC Shimla. The study was conducted over a year from 1st July 2014 to 30th June 2015. Sample size included 40 diagnosed cases of resectable gastric adenocarcinoma. All patients with operable and resectable disease were subjected to surgery and the specimen were sent for detailed histopathological examination and immunohistochemistry . χ 2 statistical analysis was performed to assess the HER-2 positivity rate . All statistics were performed using 2-sided analysis, with a significance level of p< 0.05. Results: In our study , 7 cases (17.5%) were scored as strongly positive for HER-2 membrane staining (3+), 4 cases (10%) were moderately positive (2+) and 29 cases (72.5%) were HER-2 negative (0/1+) on IHC. The positivity rates in diffuse type (22.2%) and poorly-differentiated (25%) gastric cancer were higher than those in intestinal type (9.9%) and well-differentiated (14.3%) gastric cancer respectively. Conclusions: There is a strong association of human epidermal growth factor receptor-2 positivity with Gastric Malignancy in our country especially in poorly differentiated cancers. Targeted biological therapy with Trastuzumab hence becomes an attractive addition to the multimodality therapy usually required in the treatment of locally advanced /metastatic gastric cancers.